AYURVEDIC PHARMACO-THERAPEUTIC ADOPTION OF CESTRUM DIURNUM L. (International Journal of Ayurveda and Pharma Research, 2016)
Cestrum diurnum L. known as Day jasmine, day cestrum, wild jasmine, a Solanaceae member is a native of West indies and introduced to India as an ornamental plant. The berries of the plant contain solanine, tropane-alkaloids and generally lead to acute toxicity, whereas the leaves have calcitriol (1,25- dihydroxycholecalciferol) which causes chronic toxicity in animals like cattle, horses with characteristic symptoms of vitamin D3 poisoning. However, external application of calcitriol has been approved for use in Psoriasis, and being the natural source of calcitriol C. diurnum L. becomes a potential candidate for the treatment of psoriasis. Based on the review of the literature and the field data available so far, it can be stated that, C. diurnum L. is being enthusiastically adopted by Ayurvedic physicians for the treatment of Kitibhakushta (psoriasis). An analysis of the medicine based on Ayurvedic rasapancaka (Rasa-taste, Guna-quality, Virya-potency, Vipaka-post-assimilation change, Prabhava-exclusive activity) parameters further confirms its utility as per Ayurvedic etymology. Based on the supporting evidence of C. diurnum L. extracts efficacy in psoriasis treatment its sure to take the center stage in the treatment of Psoriasis and related conditions hereafter.